2019
DOI: 10.1038/s41598-019-44131-4
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional-Like Amorphous Indium Tungsten Oxide Nano-Sheet Junctionless Transistors with Low Operation Voltage

Abstract: In this work, we have successfully demonstrated the junctionless (JL) transistors with two-dimensional-like (2D-like) nano-sheet (NS) material, amorphous indium tungsten oxide (a-IWO), as an active channel layer. The influences of the different gate insulator (GI) materials and the scalings of GI thickness, a-IWO channel thickness, and channel lengths on the a-IWO NS JL transistors (a-IWO NS-JLTs) have been studied for the purposes of low operation voltage (gate voltage ≤2V) and high performance. The 2D-like a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…To match with the measured I D -V G curves, the extracted interface N GA were 0, 8.0 × 10 12 , 8.0 × 10 13 , and 1.0 × 10 14 cm −2 eV −1 for 3%, 7%, 10%, and 13% oxygen ratios of a-IWO, respectively. Consequently, the lower the oxygen ratio of IWO, the lower the interface Gaussian acceptor trap at the front interface was elucidated by simulation, mainly contributing the remarkable experimental electrical characteristics of the a-IWO nanosheet TFT, such as near ideal S.S., small V TH , and enhanced I ON [24]. Here the possible species at the front interface could be oxygen interstitial (O i ) [33], and a simple schematic of O i is shown in the inset of Figure 3d.…”
Section: Effect Of Gaussian Acceptor Trap At Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…To match with the measured I D -V G curves, the extracted interface N GA were 0, 8.0 × 10 12 , 8.0 × 10 13 , and 1.0 × 10 14 cm −2 eV −1 for 3%, 7%, 10%, and 13% oxygen ratios of a-IWO, respectively. Consequently, the lower the oxygen ratio of IWO, the lower the interface Gaussian acceptor trap at the front interface was elucidated by simulation, mainly contributing the remarkable experimental electrical characteristics of the a-IWO nanosheet TFT, such as near ideal S.S., small V TH , and enhanced I ON [24]. Here the possible species at the front interface could be oxygen interstitial (O i ) [33], and a simple schematic of O i is shown in the inset of Figure 3d.…”
Section: Effect Of Gaussian Acceptor Trap At Interfacementioning
confidence: 99%
“…Additionally, for the gate insulator (GI), certain high-κ materials [22], such as aluminum oxide (Al 2 O 3 ) and hafnium oxide (HfO 2 ), have been deposited by atomic layer deposition (ALD) [23] with several advantages such as atomic-scaled thickness control, high film density, and superior step coverage and uniformity. Therefore, our previous study demonstrated that the integration of a HfO 2 GI and ultra-thin amorphous indium tungsten oxide (a-IWO) junctionless TFT can be achieved with promising electrical characteristics, such as high field-effect mobility (µ FE ), near ideal subthreshold swing (S.S.) (63 mV/dec), and large ON/OFF current ratios (I ON /I OFF ) (1.5 × 10 8 ) [24]. In this work, we investigate experimentally the electrical properties of nanosheet (NS) junctionless a-IWO TFT dependent on different oxygen flows during a-IWO deposition, and then deduce numerically the correlation among the chemical species, materials properties, DOS, and band diagrams by TCAD [25].…”
Section: Introductionmentioning
confidence: 99%
“…In energy storage, 2D metal oxides present prospects for supercapacitors and lithium-ion batteries by virtue of their ion-accommodating capacity and swift charge–discharge kinetics. Graphene-like metal oxides, like molybdenum oxide (MoO 2 ) and tungsten oxide (WO 3 ), have captivated considerable attention due to their semiconducting characteristics, facilitating their integration into electronic and optoelectronic devices. , Additionally, the 2D structure of metal oxides enables the creation of heterostructures by stacking distinct 2DMs, creating hybrid substances with synergistic traits. This innovation paves the way for cutting-edge technologies like flexible electronics .…”
Section: Introductionmentioning
confidence: 99%
“…Thin-film transistors (TFTs) are becoming increasingly important due to their promising development potential and broad market in the high-end panel and flexible display. Amorphous indium gallium zinc oxide (a-IGZO), out of diverse metal oxides, draws wide attention in the areas of TFTs. A-IGZO TFTs exhibit high optical transparency, high carrier mobility, and excellent uniformity, making it one of the most competitive candidates. Although the manufacturing process of a-IGZO TFTs is relatively mature, lack of appropriate technology in realizing depletion-mode (DM) a-IGZO TFTs still limits the implementation of complementary-type circuits. Whereas, circuits constructed with single-type TFTs will consume relatively high power. An effective method to address this predicament and facilitate the power reduction is to implement DM and enhancement-mode (EM) TFTs in the circuit-level design. Heretofore, several approaches to acquire DM a-IGZO TFTs have been studied, including modulating the thickness of materials, anodic oxidation, employing different back-channel capping layers, or fluorination treatment. Nevertheless, these techniques incur a significant increase in process complexity and the relatively high-temperature treatment may also affect device performance.…”
Section: Introductionmentioning
confidence: 99%